2023
DOI: 10.3389/fphar.2023.1192777
|View full text |Cite
|
Sign up to set email alerts
|

A novel T-cell exhaustion-related feature can accurately predict the prognosis of OC patients

Abstract: The phenomenon of T Cell exhaustion (TEX) entails a progressive deterioration in the functionality of T cells within the immune system during prolonged conflicts with chronic infections or tumors. In the context of ovarian cancer immunotherapy, the development, and outcome of treatment are closely linked to T-cell exhaustion. Hence, gaining an in-depth understanding of the features of TEX within the immune microenvironment of ovarian cancer is of paramount importance for the management of OC patients. To this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Meanwhile, as shown in Fig. 4 D, the learning curve revealed that the training and validation sets were well-fitting and stable [ 26 – 28 ]. As a result, the above results revealed that the XGBoost algorithm might be employed for this dataset's classification modeling purpose.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, as shown in Fig. 4 D, the learning curve revealed that the training and validation sets were well-fitting and stable [ 26 – 28 ]. As a result, the above results revealed that the XGBoost algorithm might be employed for this dataset's classification modeling purpose.…”
Section: Resultsmentioning
confidence: 99%
“…Broadly speaking, the “estimate” package was employed to evaluate aspects like tumor purity, immune activity, and stromal characteristics. As for estimating the TME specifically, the following approaches were utilized: (1) multiple algorithms including XCELL, MCPCOUNTER, CIBERSORT, CIBERSORT-ABS, EPIC, and TIMER were applied respectively to assess immune responses [ 34 ]; (2) the immune-related processes were estimated by “‘ssGSEA”; (3) the expression levels of common ICGs were collected and compared; (4) the condition of signaling pathways, encompassing those pertinent to immunity and metabolism, was gauged using the “ssgsea” method; (5) the states of common cell deaths were also estimated through “ssgsea”. Finally, the drug sensitivity in different KIRC subtypes was investigated by “oncoPredict”.…”
Section: Methodsmentioning
confidence: 99%
“…CISD3 has also garnered attention as a result of its role in tumorigenesis 15 . Research has shown a significant upregulation of CISD3 expression in diverse cancers such as liver cancer, lung cancer, breast cancer, and colorectal cancer 18–20 . The upregulation of CISD3 may be linked to tumor cell growth, proliferation, and metastasis 18 .…”
Section: Introductionmentioning
confidence: 99%
“…15 Research has shown a significant upregulation of CISD3 expression in diverse cancers such as liver cancer, lung cancer, breast cancer, and colorectal cancer. [18][19][20] The upregulation of CISD3 may be linked to tumor cell growth, proliferation, and metastasis. 18 Although our understanding of the functionality and mechanisms of the NEET family in tumors remains limited, these research findings underscore the critical regulatory role of NEET family proteins in tumor initiation and progression.…”
mentioning
confidence: 99%